Short Communication: New records of Mactra clams (Bivalvia: Mactridae) from Madura Island, Indonesia - CATHERINE BERLIANA WIJAYA; RENI AMBARWATI; NUR ROHMATIN ISNANINGSIH (Society for Indonesian Biodiversity, 2023)
Abstract. Wijaya CB, Ambarwati R, Isnaningsih NR. 2023. Short Communication: New records of Mactra clams (Bivalvia: Mactridae) from Madura Island, Indonesia. Biodiversitas 24: 6684-6691. Mactridae is a family of bivalves found in shallow waters, such as living at high tide lines, in tidal areas, and below low tide lines. More mactrid bivalves could be discovered, and further studies are needed in Indonesian waters. Madura Island has a variety of bivalves, and Mactra clams could also be discovered on this island. Therefore, this study aimed to identify Mactra clams from Madura Island, Indonesia, and analyze their morphological characters. Samples were collected at Nepa and Badur Beaches during low tides, and then identified based on morphological characteristics. A stereo microscope observation and detailed descriptions were carried out to obtain the qualitative characteristics, while the quantitative ones, included shell length and height, palial line height, and diameter. The environmental parameters of this two-beach were also evaluated. Data were analyzed descriptively. The results showed two new records of Mactridae members at both beaches, namely Mactra luzonica Reeve, 1854, Mactra dissimilis Reeve, 1854. Mactra dissimilis revealed morphological variation, namely in the coloration on both the exterior and interior of the shell. There were three variations of M. dissimilis, namely bluish-white shell, brownish-white shell, and white shell. The findings of M. dissimilis and M. luzonica are regarded as new records for Madura Island, Indonesia.